Recurso educativo y aprendizaje de Bioseguridad dirigido a estudiantes de Medicina de la Universidad Nacional de Loja - Navarro Novillo, Marlon David (2025)
Biosafety comprises a set of strategies and procedures aimed at preventing risks associated with biological, physical and chemical agents, in order to guarantee the safety of the patient, health personnel and the environment. In this context, higher education institutions have the responsibility to implement innovative and effective teaching methods that favor the development of competencies in students, allowing them to acquire the necessary skills for their performance in different professional fields. This prospective cross-sectional cohort study, of a qualitative and quantitative nature, aimed to implement a simulation workshop focused on Biosafety, aimed at medical students of the National University of Loja. To this end, an easy-to-understand practical clinical guide was developed, designed to reinforce the students' knowledge, and an educational video recorded in the Faculty's Procedures laboratory was produced, aligned with the parameters and objectives of the subject. Subsequently, the simulation workshop was given, and the knowledge acquired through two Structured Objective Clinical Exams (OSCE) applied to 38 students was evaluated. In the first OSCE, carried out without educational resources, the results were as follows: 26.32% (n=10) obtained a rating of "very good", 57.89% (n=22) achieved "good", 10.53% (n=4) obtained "fair", and 5.26% (n=2) "insufficient". After the implementation and review of educational resources, the second OSCE showed a significant improvement in performance: 84.21% (n=32) achieved a rating of "outstanding", 10.53% (n=4) obtained "very good", and 5.26% (n=2) "good". This analysis concludes that the planning, execution and dissemination of educational resources, together with the implementation of the clinical simulation workshop, favored the development and enrichment of students' knowledge on Biosafety, proving to be an innovative and effective methodology in medical training through clinical simulation